Empirical Eigenfunctions and Medial Surface Dynamics of a Human Vocal Fold - Döllinger, M.; Tayama, N.; Berry, D. A. (Methods of Information in Medicine, 2005)
Objectives: The purpose of this investigation was to use an excised human larynx to substantiate physical mechanisms of sustained vocal fold oscillation over a variety of phonatory conditions. During sustained, flow-induced oscillation, dynamical data was collected from the medial surface of the vocal fold. The method of Empirical Eigenfunctions was used to analyze the data and to probe physical mechanisms of sustained oscillation.Methods: Thirty microsutures were mounted on the medial margin of a human vocal fold. Across five distinct phonatory conditions, the vocal fold was set into oscillation and imaged with a high-speed digital imaging system. The position coordinates of the sutures were extracted from the images and converted into physical coordinates. Empirical Eigenfunctions were computed from the time-varying physical coordinates, and mechanisms of sustained oscillation were explored.Results: Using the method of Empirical Eigenfunctions, physical mechanisms of sustained vocal fold oscillation were substantiated. In particular, the essential dynamics of vocal fold vibration were captured by two dominant Empirical Eigenfunctions. The largest Eigenfunction primarily captured the alternating convergent/ divergent shape of the medial surface of the vocal fold, while the second largest Eigenfunction primarily captured the lateral vibrations of the vocal fold.Conclusions: The hemi-larynx setup yielded a view of the medial surface of the vocal folds, revealing the tissue vibrations which produced sound. Through the use of Empirical Eigenfunctions, the underlying modes of vibration were computed, disclosing physical mechanisms of sustained vocal fold oscillation. The investigation substantiated previous theoretical analyses and yielded significant data to help evaluate and refine computational models of vocal fold vibration.
Keywords: Human vocal folds; medial surface dynamics; empirical eigenfunctions; hemi-larynx; sustained phonation; nonlinear dynamics